2016
DOI: 10.1007/s00417-016-3461-4
|View full text |Cite
|
Sign up to set email alerts
|

Internal limiting membrane transplantation for unclosed and large macular holes

Abstract: Transplantation of autologous ILM is an effective addition to the surgical options for large macular holes after failed surgeries with ILM removal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(40 citation statements)
references
References 14 publications
1
37
0
2
Order By: Relevance
“…Many techniques have been proposed to increase closure rate in recurrent HMMH with RD, such as autologous blood (Lai et al 2015), ILM free patch (Morizane et al 2014;Dai et al 2016;Chen et al 2018) and retinal autograft (Grewal & Mahmoud 2016;Wu et al 2018). The purpose behind these techniques was to find a substrate to seal the MH in order to prevent fluid passing through the MH to the subretinal space, and to allow tissue proliferation in order to obtain retinal restoration and VA recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Many techniques have been proposed to increase closure rate in recurrent HMMH with RD, such as autologous blood (Lai et al 2015), ILM free patch (Morizane et al 2014;Dai et al 2016;Chen et al 2018) and retinal autograft (Grewal & Mahmoud 2016;Wu et al 2018). The purpose behind these techniques was to find a substrate to seal the MH in order to prevent fluid passing through the MH to the subretinal space, and to allow tissue proliferation in order to obtain retinal restoration and VA recovery.…”
Section: Discussionmentioning
confidence: 99%
“…In 2010, Michalewska et al [12] reported an inverted ILM flap technique that improved both the functional and anatomical results for large MHs. In 2016, Dai et al [13] reported a free-flap transplantation of an autologous ILM for large MHs. However, these techniques cannot be applied when the ILM has already been removed in a previous surgery.…”
Section: Introductionmentioning
confidence: 99%
“…This fluid, combined with the movement of the globe, could produce turbulence, which may dislocate the ILM flap from the MH after surgery. Thus, retinal glue such as OVD to stabilize the ILM flap has been used to resolve the problem [5,7,11,12]. However, OVD application onto MH or ILM is challenging in a fluid-filled eye.…”
Section: Discussionmentioning
confidence: 99%